ORGANIZATIONAL AND LEGAL DISTRIBUTION OF FINANCIAL RESOURCES THE UNITED TERRITORIAL COMMUNITY IN THE CONTEXT OF SECURITY CONDITIONS - GEVKO, VOLODYMYR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In modern transformational conditions, the formation of Ukrainian statehood with the choice of the European course of urgency is gaining the issue of budget decentralization, where the key figures are the efficiency of local governments. In this regard, there is a problem of optimal redistribution of financial resources and powers of local authorities, which today are the main and most relevant for improving the efficiency of the budget system as a whole, because the effectiveness of socio-economic policy and its economic security directly depend on rational built and balanced system of economic relations, a clear redistribution of financial resources and flexibility of ways to use them. The article conducts a comprehensive study the mechanism of distribution financial resources the united territorial community in the context of security. The system of management balanced development the united territorial community on the basis of application of safety conditions is substantiated. It is proposed to consider the distribution of budget funds in the territorial community depending on the area, the number of rural residents and the actual income of village (settlement) for the relevant period. Two projects of algorithm calculation the budget with separation of main stages are formed.